Innovation Policy Impact on Technologically Advanced Industries in Overseas France Departments - Dorocki, Sławomir; Brzegowy, Paweł (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2013)
The goal of the study is to present the innovative attractiveness of the extra-European departmentsand regions of France (DROM): Guadeloupe, Martinique, French Guiana and Réunion. On thebasis of the Regional Innovation Strategies - Stratégie Régionale d’Innovation (SRI) - and initiativesof Synergîle, Capenergies and others, the direction of the implemented investments will be presented,as well as effective creation of research-business synergy and prospects of its further intensificationduring economic recession. Such factors as acceleration of knowledge creation, accessibility of basiccommunication techniques or systems of flexible specialization - which are the primary determiners ofa knowledge-based economy spatial formation - are subject to analysis and assessment. The process ofits formation in the DROM regions results from the materialization of the Lisbon Strategy and Europe2020 programme guidelines. The example of the Overseas France proves that technologically advancedindustries may not only be localized in metropolitan areas, but also in peripheral regions, traditionallyviewed as less attractive ones. Moreover, the DROM regions remain to be an exemplification of the ‘learning region’ concept, which is proved by the effective involvement of particular innovation centresin the promotion of modern branches of industry.